Guest

A wave y = asin(ωt −kx) on a string meets with another wave producing a node at x = 0.Then the equation of the unknown wave is (a) y = asin(ωt + kx) (b) y = −asin(ωt +kx) (c) y = asin(ωt −kx) (d) y = −asin(ωt −kx)

A wave y = asin(ωt −kx) on a string meets with another wave producing a node at x = 0.Then
the equation of the unknown wave is
(a) y = asin(ωt + kx) (b) y = −asin(ωt +kx)
(c) y = asin(ωt −kx) (d) y = −asin(ωt −kx)

Grade:7

1 Answers

Vikas TU
14149 Points
6 years ago
let the other string eqn. be,
y = asin(wt + kx)
put x=0 in first wave eqn.
we get,
y = asin(wt)
equate both,
asin(wt + kx) – asinwt =0
a(sin(wt +kx) – sinwt) = 0
a cannot be zero.
solve then second one by applying sinC – sinD formulae.
and then find the soln. and cross check wth the options.
 

Think You Can Provide A Better Answer ?